Hemicraniectomy for malignant middle cerebral artery infarction: retrospective consent to decompressive surgery depends on functional long-term outcome - Kiphuth, Ines C.; Köhrmann, Martin; Lichy, Christoph; Schwab, Stefan; Huttner, Hagen B. (Neurocritical care, 2010)
Decompressive surgery for malignant middle cerebral artery infarction increases the number of surviving patients; this, however, leaves some patients severely disabled. This study analyzed the patients’ retrospective consent to hemicraniectomy in light of the experienced functional outcome 12 months after hospital stay.
Gesehen am 09.03.2023